Causal Association Between 12 Micronutrients and Common Chronic Respiratory Diseases: A Bidirectional Two-Sample Mendelian Randomization Study - Tingting Zhu; Xiuyun Chen; Qing Wang; Fang Li; Junjun Yang; Xinyu Zhu; Jingmei Wang; Jixiang Bo (Genetics Research)
Conclusion: This study shows significant causal associations among calcium, vitamin B12, and vitamin E with chronic respiratory diseases. There is a bidirectional protective causal relationship between calcium and asthma, suggesting that increasing calcium intake may reduce the risk of asthma. However, the causal relationships among other vitamins, minerals, and chronic respiratory diseases remain inconclusive, necessitating further research to validate these findings’ robustness and generalizability.